Media coverage and Its Determinants in the Context of the COVID-19 Pandemic - Gálik, Slavomír; Gáliková Tolnaiová, Sabína (Communication Today, 2022)
This study covers the issue of information dissemination. Along with recognising this topic in the social epistemology framework, the authors aim to identify and analyse the circumstances and significant factors that determine it in the context of the COVID-19 pandemic. They uncover certain risks in terms of achieving the very objectives of disseminating information via the media.In the first part, the authors outline the process’s essence and nature, but also its social value in the current pandemic situation. They make a particular reference to the role of journalism, or rather journalists in their specific professional and personal circumstances (broader and global communication ecology that concerns the pandemic with a direct news cycle, or social media and layman media practices and, for example, also the financing issues or insecurity of the profession, economic conditions, etc.). In the second part, they identify the determining factors influencing media coverage – its technological context – space and time, but also ethical and noetic factors related to journalists. They draw attention to relations and interactions that shape the specific character of media-disseminated information and bring risks (‘information explosion’ in society, including “(dis)infodemic”, the professional noetic crisis in connection with the crisis of relevant concepts in journalism and the quality of journalists’ work, but also the ethical crisis in the context of non-ethical interests and relations in the media (ideological, political, economic), journalists’ personal moral failures and their own neglect of epistemic (cognitive) training in the context of professional practice, etc.) for the public, concerning its aim to contribute to the reduction of social uncertainty, fear, risk of fear and panic, or to the correct and ethical judgement and action of the public at the time of the pandemic.